ENGINEERING THE ENERGY TRANSITION: RENEWABLE ENERGY INNOVATIONS, APPLICATIONS, AND FUTURE TRENDS IN SOUTH KOREA AND UZBEKISTAN - Diyorbek Norqulov (World Scientific Research Journal, 2025)
The global shift toward renewable energy is reshaping the mission of mechanical engineering. Rising electrification, net-zero mandates, and digitalization demand systems that are efficient, durable, and software-defined. This article examines how renewable energy systems advance through mechanical design, AI-enabled optimization, and smart-grid integration, using South Korea and Uzbekistan as complementary case studies. South Korea combines major Green New Deal investments, smart-grid development plans, and close collaboration between universities and industries to support the fast expansion of energy storage systems, hydrogen infrastructure, and large-scale solar and wind projects. Uzbekistan, meanwhile, is executing a fast transition: leadership has raised the 2030 renewable electricity target to 54%, paired with grid modernization and utility-scale solar/wind build-outs. Bilateral links — IT Park Uzbekistan’s Seoul office, joint forums, and technical cooperation — create a practical corridor for technology transfer and workforce development. The paper argues that engineers fluent in digital twins, predictive maintenance, power electronics, thermal/structural reliability, and lifecycle carbon analysis will be central to scaling renewables. A forward-looking roadmap outlines how policy, R&D, and industrial pilots can align to accelerate deployment while safeguarding system stability and cost. South Korea provides a replicable template; Uzbekistan offers a proving ground. Together they form a regional engine for the energy transition.